2006
DOI: 10.1111/j.1439-0396.2005.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a probiotic Enterococcus faecium strain supplemented from birth to weaning on diarrhoea patterns and performance of piglets*

Abstract: This placebo-controlled double-blind study was conducted to evaluate effects of Enterococcus faecium DSM 10663 NCIMB 10415 (EcF) orally given from birth to weaning on diarrhoea and performance of piglets. At the first 3 days postnatum (p.n.), piglets from 54 [verum group (VG)] and 60 [placebo group (PG)] sows got 1 g of a gel directly per mouth by a dosing device. Gel for the VG contained 2.8 x 10(9) colony forming units (CFU) EcF/g. From day 4 p.n. until weaning (24 +/- 3.2 days p.n.) a liquid additive was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 30 publications
2
64
0
2
Order By: Relevance
“…Other studies reported a reduction in the level of pathogenic intestinal bacteria after application of Enterococcus spp. to test animals (24,26,34) and a reduction in diarrhea in piglets (36,44). However, negative effects on the intestinal flora have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported a reduction in the level of pathogenic intestinal bacteria after application of Enterococcus spp. to test animals (24,26,34) and a reduction in diarrhea in piglets (36,44). However, negative effects on the intestinal flora have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies using E. faecium NCIMB 10415 showed that diarrhea was reduced and performance increased (Taras et al 2006;Zeyner and Boldt, 2006;BĂŒsing and Zeyner, 2015) whereas others did not (Broom et al 2006;Martin et al 2012). It was initially shown that E.…”
Section: Prevention Of Diarrheamentioning
confidence: 99%
“…Enterococcus faecium NCIMB 10415, a probiotic that can reduce diarrhea incidence in piglets (BĂŒsing and Zeyner, 2015;Zeyner and Boldt, 2006), has been investigated in ETEC-infected IPEC-J2 cells, to deepen insight on the mechanisms underlying the bacterial-epithelial crosstalk during innate immune responses triggered by enteric infections. ETEC decreased transepithelial resistance (TEER) and increased IL-8 expression, and this effect could be prevented by both pre-incubation and simultaneous addition with E. faecium for up to 4 h Lodemann et al 2015).…”
Section: Probiotics Used In Pig Intestinal Cells Challenged With Etecmentioning
confidence: 99%
“…In addition, numerous institution-based experiments (as opposed to real farm conditions) have shown that in-feed antimicrobials are at their most effective in animals being raised under sub-optimal conditions (Dritz et al, 2002). Where high welfare, high health status animals are used, as in agricultural research centres, the gains produced by in-feed antimicrobials are marginal, at best (Zeyner and Boldt, 2006). These findings may inform subsequent research into the efficacy of probiotics.…”
Section: Do Probiotics Work? -An Overviewmentioning
confidence: 99%